The Management Company Intangible Assets Governance in Pharmaceutical Industry (Journal of Pharmaceutical Negative Results, 2022)
This article attempts to answer the management company intangible assets governance in pharmaceutical industry. In this study, we use pure literature survey and conclusions are drawn from theoretical analysis and discussion results. This research will add depper insight intangible assets governance in pharmaceutical industry. The right intangible assets are considered as the root of the company's value creation, helping the company to achieve success. In addition, intangible assets are one of the main sources of competitive advantage.